(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
This study examines the critical role of family support in shaping the well-being, integration, and success of visually impaired persons. Focusing on both positive and negative family dynamics, the research investigates how family support—or its absence—impacts the personal and social development of visually impaired persons from childhood through adulthood. Positive family support is shown to enhance resilience, promote emotional stability, and facilitate social integration, ultimately fostering self-sufficiency and economic independence in visually impaired persons. In contrast, a lack of family support correlates with reduced well-being, emotional instability, and challenges in social integration, often leading to feelings of loneliness and frustration. The study sampled 70 respondents from special institutions in Punjab through a simple random sampling method, collecting data via structured interviews. Findings reveal that visually impaired persons with strong family support exhibit better social adjustment, broader social networks, and minimal psycho-social difficulties. These results underscore the importance of equipping parents with awareness and skills to provide sustained, positive support, recognizing the distinct needs of their visually impaired children.